Study on the Management Way of “Banning Electric Bicycles from Going Upstairs” in Tianjin - Haolun Mou; Jingyang Sun; Yan Pan; Junzheng Wang; Zhen Wang; Jiayi Qin (Studies in Law and Justice, 2023)
In recent years, the number of electric bikes in Tianjin is close to 4.59 million. Since 2018, there have been 241 electric bicycle fires in Tianjin, with direct property losses of 1.36 million yuan. Although the newly revised “Tianjin Fire Control Regulations” was officially implemented on November 9, 2021, the problems of unclear division of management rights and responsibilities and weak law enforcement force have been unable to be solved. Through literature collection, questionnaire survey, grassroots research and other methods, the paper inspects the implementation of relevant policies in Tianjin residential communities, summarizes the outstanding problems, carries out the grass-roots law publicity, and puts forward a series of specific measures.